Influence of base impurity distribution on the photoelectric properties of surface-barrier UV photodetectors - Bobrenko, Yu. N.; Komaschenko, V. N.; Yaroshenko, N. V.; Sheremetova, G. I.; Atdaev, B. S. (Technology and design in electronic equipment, 2012)
The article presents the study on spectral, capacitance-voltage and current-voltage characteristics of surface-barrier structures based on A2B6 composition with different carrier concentration profiles in space-charge region sensitive to ultraviolet range and perspective for ultraviolet sensor application.